Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Kelas X di SMK Dr. Indra Adnan Indragiri Collage Menggunakan Metode AHP - Niswah, Muhlishatun; Nuraini (Indra Institute Research & Publication, 2024)
Selecting outstanding students at Dr.Indra Adnan Indragiri Collage Vocational High School is an important activity in improving the quality of education. This process is always done manually and takes a lot of time. Therefore, a decision support system using the Analytical Hierarchy Process (AHP) method is needed to facilitate the selection of outstanding students. This research aims to appoint outstanding students at SMK Dr. Adnan Indragiri Collage according to the criteria determined through decision support system techniques. This multi-criteria decision-making technique is based on the theory that each choice consists of a set of valid criteria and each criterion has a weight that describes its importance relative to other criteria. The calculation results show that there is one (1) student who can be used as a suggestion from the three (3) data used by researchers. This student is abbreviated as A1 with the highest score of 0.567.